Periodization for Mixed Martial Arts - James, L. P.; Kelly, V. G.; Beckman, E. M. (Strength and Conditioning Journal, 2013)
The mixed martial artist requires the development of a broad scope of divergent physiological abilities to compete successfully. To minimize any potential interference effects and optimize training adaptations, a periodized training plan is needed to manage the integration of this sport's many training stressors. This article provides guidelines and practical examples for the strength and conditioning coach.